Rectification in nonequilibrium steady states of open many-body systems - Kazuki Yamamoto; Yuto Ashida; Norio Kawakami (Physical Review Research, 2020)
We study how translationally invariant couplings between many-particle systems and nonequilibrium baths can be used to rectify particle currents, for which we consider minimal setups to realize bath-induced currents in nonequilibrium steady states of one-dimensional open fermionic systems. We first analyze dissipative dynamics associated with a nonreciprocal Lindblad operator and identify a class of Lindblad operators that are sufficient to acquire a unidirectional current. We show that unidirectional particle transport can, in general, occur when a Lindblad operator is reciprocal provided that the inversion symmetry and the time-reversal symmetry of the microscopic Hamiltonian are broken. We demonstrate this mechanism on the basis of both analytical and numerical approaches, including the Rashba spin-orbit coupling and the Zeeman magnetic field.